2022
DOI: 10.1002/btpr.3239
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation and differentiation of primary bovine myoblasts using Chlorella vulgaris extract for sustainable production of cultured meat

Abstract: Recently, cultured meat obtained from livestock-derived cells is being considered as a sustainable food source that reduces the use of natural resources. This study aimed to show that nutrients extracted from Chlorella vulgaris were beneficial in the culture of primary bovine myoblasts (PBMs), a major cell source for cultured meat production. Nutrients (glucose, amino acids, and vitamins) present in the animal-cell culture media were effectively recovered from C. vulgaris using acid hydrolysis treatment. On cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 29 publications
2
24
0
Order By: Relevance
“…When algae extract (CVE) was combined with growth factors, insulin and other additives, a similar marginal increase in cell viability of around 20% was observed in an environment where cells were already dividing. These observations of an increase in viability caused by CVE in both diving and non-dividing environments are consistent with other studies (Okamoto et al 2022), suggesting that CVE increases cell viability independent of effects on proliferation. The possibility that algae extract enhances the cellular metabolic potential without promoting cell division requires further investigation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…When algae extract (CVE) was combined with growth factors, insulin and other additives, a similar marginal increase in cell viability of around 20% was observed in an environment where cells were already dividing. These observations of an increase in viability caused by CVE in both diving and non-dividing environments are consistent with other studies (Okamoto et al 2022), suggesting that CVE increases cell viability independent of effects on proliferation. The possibility that algae extract enhances the cellular metabolic potential without promoting cell division requires further investigation.…”
Section: Discussionsupporting
confidence: 93%
“…In another study, researchers reported high levels of glucose and amino acids present in various microalgae extracts, with particularly high levels of aspartate and glutamate detected in extract from C. vulgaris (Okamoto et al 2020); these authors proceeded to show that they could use such algae extracts as a substitute to culture cells in media deficient in glucose and amino acids. More recently, this same group showed that C. vulgaris extract can be used as a replacement for DMEM in the culture of primary bovine myoblasts (Okamoto et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…These results confirm the need to further study the composition of cultured meat medium and additives to improve the taste of CMT. Okamoto et al (2022) used autotrophic microalgae to promote the growth of bovine myoblasts for producing cultured meat. Chlorella vulgaris was subjected to acid hydrolysis to extract nutrients (CVE, Chlorella vulgaris extract) that could be used in the medium.…”
Section: Current Technologies In the Development Of Cultured Meatmentioning
confidence: 99%
“…After C. littorale was cultured in the mammalian cell waste medium for 48 h in the first and second cycles, the microalgae were harvested by centrifugation (2300 × g and 5 min). Nutrients were extracted from the microalgae using hydrochloric acid, as previously described (Okamoto et al 2020 and 2022 ). Briefly, the microalgae were treated with 0.5 N hydrochloric acid (Fujifilm Wako Pure Chemical, Osaka, Japan) at a concentration of 330 g (wet weight)/L at 100℃ for 24 h. After neutralization using sodium hydroxide (Fujifilm Wako Pure Chemical) and centrifugation (12,500 × g and 5 min), the supernatant was harvested and used for mammalian cell culture.…”
Section: Methodsmentioning
confidence: 99%
“…To address this issue, we propose a novel mammalian cell culture system using microalgae. We have previously reported that mammalian cells can be cultivated using nutrients extracted from microalgae (Okamoto et al 2020 and 2022 ). In addition, we have also demonstrated successful microalgal culture in mammalian cell waste medium (Haraguchi and Shimizu 2021 ).…”
Section: Introductionmentioning
confidence: 99%